Potential of surfactant washing to solve drilling waste environmental problems offshore - Muherei, M. A.; Junin, Radzuan (2007)
Offshore direct discharge is a simple and economically feasible method in which the contaminated drill cuttings are released to the environment onsite. Recently, disposal of oily drilling waste is strictly regulated. Allowable oil on cuttings particularly offshore is set at limits far difficult for current cleaning technologies to deal with. Therefore there is an urgent need to develop cost-effective methods for cleaning oilwell contaminated drill cuttings and grant their direct discharge offshore. Surfactant-enhanced washing is being considered with increasing frequency to actually achieve contaminant removal. This paper reviews most important factors affecting contaminant removal by surfactants. It has been shown that enhanced surfactant washing normally occurred at surfactant concentrations below and above the CMC indicating the occurrence of both oil drop rollup and/or snapoff and solubilization mechanisms. The later mechanism is greatly enhanced with lower CMC surfactants and the first mechanism with surfactants possessing lower interfacial tensions. In certain cases the lower CMC of nonionic surfactants made them attractive candidates while in other cases the lower sorption and higher solubilization potential of selected anionic surfactants made them the preferred choice. Evaluation of surfactants are based on examining the ability of the surfactant to maintain lower interfacial tension between target contaminant and water, satisfying lower CMCs, and sustaining lower sorption and precipitation to target substrate. Surfactant mixtures of anionic and nonionic surfactant are shown to be excellent candidates for robust surfactant cleaners.